2008
DOI: 10.1111/j.1863-2378.2008.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR and RPLA Identification of Staphylococcus aureus Enterotoxigenic Strains From Bulk Tank Milk

Abstract: Enterotoxigenic Staphylococcus aureus in raw milk poses a potential health hazard to consumers, and the identification of such strains should be used as part of a risk analysis of milk and milk products. The primary purpose of this study was to investigate the occurrence of enterotoxigenic S. aureus strains in raw milk supplied for dairy processing in the Czech Republic. A further aim was to compare the production of staphylococcal enterotoxins (SEs) with the presence of the corresponding genes. This was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 31 publications
8
39
3
Order By: Relevance
“…Similar data were reported by Zouharova and Rysanek (2008) in bulk tank cow's milk samples (15.9%). MRSA was found only in goat's milk samples and the irregular detection of MRSA in bulk tank milk samples was probably due to substantial dilution of contaminated milk and thus to substantially reduced likelihood of MRSA detection.…”
Section: Discussionsupporting
confidence: 78%
“…Similar data were reported by Zouharova and Rysanek (2008) in bulk tank cow's milk samples (15.9%). MRSA was found only in goat's milk samples and the irregular detection of MRSA in bulk tank milk samples was probably due to substantial dilution of contaminated milk and thus to substantially reduced likelihood of MRSA detection.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, several studies reported that none of the strains isolated from bovine and CM and dairy products harbored the seb gene (Akineden et al 2001;Lyra et al 2013). In other studies, however, the seb gene was detected in S. aureus isolates from milk and dairy products at various frequencies (Jørgensen et al 2005;Zouharova and Rysanek 2008). The fact that seb was the most commonly detected SE genotype in isolates from OM in our study is in agreement with the findings of previous studies (Arcuri et al 2010;Peles et al 2007).…”
Section: Detection Of Se and Tst Genessupporting
confidence: 83%
“…None of the strains in our study harbored the see gene, in agreement with other investigations on S. aureus isolates from milk and dairy products (Arcuri et al 2010;Carfora et al 2015;Cremonesi et al 2007;Jørgensen et al 2005;Poli et al 2007;Zouharova and Rysanek 2008).…”
Section: Detection Of Se and Tst Genessupporting
confidence: 79%
See 2 more Smart Citations